CNTM-04. Alterations in structural connectomic properties associated with neurocognitive changes following glioma resection. (12th November 2021) - Noll, Kyle; Mitchell, Drew; Chen, Henry; Wefel, Jeffrey; Kumar, Vinodh; Hou, Ping; Ferguson, Sherise; Rao, Ganesh; Johnson, Jason; Schomer, Donald; Prabhu, Sujit; Liu, Ho-Ling
Abstract: BACKGROUND: Patients with brain tumors often experience decline in neurocognitive functioning (NCF) following surgical tumor resection. Connectomic studies have begun to uncover how abnormalities to underlying cerebral networks contribute to NCF deficits; however, few studies have investigated relationships between pre- to postoperative changes in structural connectomics and NCF. METHODS: Fifteen right-handed adults with left perisylvian tumors underwent MRI of the brain with diffusion tensor imaging (DTI) and neuropsychological assessment before and after awake tumor resection. Graph theoretical analysis was applied to DTI-derived connectivity matrices to calculate structural network properties. Structural network properties and NCF measures were compared across the pre- to postoperative periods with matched pairs Wilcoxon signed-rank tests. Associations between pre- to postoperative change in network properties and change in NCF were determined with Spearman rank-order correlations (ρ). RESULTS: Nearly 90% of the sample showed postoperative decline on 1 or more NCF measures. Significant postoperative NCF decline was found across measures of verbal memory, processing speed, executive functioning, receptive language, and the Clinical Trial Battery Composite (CTB COMP) index. Regarding connectomic properties, significant postoperative changes were observed in global and local efficiency, characteristic path length, clustering coefficient, betweenness centrality, and assortativity, with medium effect sizes. Significant associations (ρ = .59 to .62, all p < .05) were observed between changes in aspects of NCF and connectomic properties. CONCLUSIONS: Decline in NCF was common following resection and some postoperative outcomes were associated with changes in structural connectomic properties following surgery.